Kepuasan Kerja Dipengaruhi Oleh Kepemimpinan, Komunikasi, Dan Motivasi Pada Perusahaan Umum Daerah Tirta Manuntung Balikpapan - Ramadyah Noviani, Putri; Hadiyatno, Didik; Cahyaning Putri Cipto, Rahajeng (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
The purpose of this study is to determine the influence of Leadership, Communication, and Motivation on Employee Job Satisfaction in the Tirta Manuntung Balikpapan Regional Public Company. The type of research used is quantitative research. The sampling technique in this study is purposive sampling with a sample of 104 permanent employees at the Tirta Manuntung Balikpapan Regional Public Company. The data collection method was carried out by field observation and questionnaire distribution. This research uses SmartPLS in processing data. The results of this study show that the leadership variable has no partial effect on employee job satisfaction at the Tirta Manuntung Balikpapan Regional Public Company, the communication variable has no partial effect on the employee job satisfaction of the Tirta Manuntung Balikpapan Regional Public Company, and the motivation variable has a partial effect on the job satisfaction of employees of the Tirta Manuntung Balikpapan Regional Public Company.